Wykonaj redukcję wyrazów podobnych i oblicz wartości liczbowe wyrażeń:

a) 2[4x - (4y + 3x)] - 4[3x - (2x - 3y)] =


dla x = -3,5 i y= 5/6


b) a - 2(b - 1) + 2[ -5(a+1) - 0,5a] + 2b =


dla a = 4/5 i b = 1/4


c) 3x - 2(-5 + y) - 5[-3x + 2(y - 1)] - 10(5y - 4) =



dla x = -1/3 i y = -4

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-05T20:15:38+01:00
A) 2[4x - (4y + 3x)] - 4[3x - (2x - 3y)] =
2[4x - 4y - 3x] - 4[3x - 2x +3y]=
8x-8y-6x-12x+8x-12y=-2x-20y=-2*(-3,5)-20*(5/6)=
7-50/3=21/3-50/3=-29/3


dla x = -3,5 i y= 5/6


b) a - 2(b - 1) + 2[ -5(a+1) - 0,5a] + 2b =
a - 2b +2 + 2[ -5a-5 - 0,5a] + 2b =
a-2b+2-10a-10-a+2b=-10a-8=-10(4/5)=-8


dla a = 4/5 i b = 1/4

c) 3x - 2(-5 + y) - 5[-3x + 2(y - 1)] - 10(5y - 4) =
3x +10 -2 y - 5[-3x + 2y - 2] - 50y +40 =
3x+10-2y+15x-10y+10-50y+40=
18x-62y+60=18*(-1/3)-62*(-4)+60=
-6+248+60=302


dla x = -1/3 i y = -4
1 5 1
2010-02-05T20:37:25+01:00
A)2[-14-(10/3-10,5)]-4[-10,5-(-7-5/2)]= =2(-14+43/6)-4(-10,5+9,5)=-28+43/3+42-38=-29/3
b)4/5-2(1/4-1)+2[-5(4/5+1)-0,5*4/5]+2*1/4=
=4/5-1/2+2+2(-4-5-2/5)+1/2=2,3-8-10-4/5+1/2=-16
c)3*(-1/3)-2(-5-4)-5[1+2(-4-1)]-10(-20-4)=
=-1+10+8-5(-11)+200+40=17+55+200+40=312
2010-02-05T20:58:44+01:00
A) 2[4x - (4y + 3x)] - 4[3x - (2x - 3y)] =
2[4x - 4y - 3x] - 4[3x - 2x +3y]=
8x-8y-6x-12x+8x-12y=-2x-20y=-2*(-3,5)-20*(5/6)=
7-50/3=21/3-50/3=-29/3

dla x = -3,5 i y= 5/6

b) a - 2(b - 1) + 2[ -5(a+1) - 0,5a] + 2b =
a - 2b +2 + 2[ -5a-5 - 0,5a] + 2b =
a-2b+2-10a-10-a+2b=-10a-8=-10(4/5)=-8

dla a = 4/5 i b = 1/4

c) 3x - 2(-5 + y) - 5[-3x + 2(y - 1)] - 10(5y - 4) =
3x +10 -2 y - 5[-3x + 2y - 2] - 50y +40 =
3x+10-2y+15x-10y+10-50y+40=
18x-62y+60=18*(-1/3)-62*(-4)+60=
-6+248+60=302

dla x = -1/3 i y = -4